2020
DOI: 10.1038/s41598-020-71421-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome diversity of Chinese indigenous chicken and the selective signatures in Chinese gamecock chicken

Abstract: Gamecock chickens are one of the earliest recorded birds in China, and have accumulated some unique morphological and behavioral signatures such as large body size, muscularity and aggressive behavior, whereby being excellent breeding materials and a good model for studying bird muscular development and behavior. In this study, we sequenced 126 chicken genomes from 19 populations, including four commercial chicken breeds that are commonly farmed in China, 13 nationwide Chinese typical indigenous chicken breeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 52 publications
4
46
1
Order By: Relevance
“…As the efficiency of this analysis relies on heterozygotes across genomes [ 39 ], the result from low-coverage genomes is unreliable. The number of high-coverage genomes in 1K CGP is limited [ 27 ], so we also included recently published chicken genomes [ 35 , 40 , 41 ] with a coverage of ≥ 20-folds in this analysis (Additional file 1 : Table S1). Our data contain genomes from GGS and 18 chicken populations including commercial breeds (White Leghorn, White Recessive Rocks, Rhode Island Red, and Cobb chicken), Ethiopian, Sri Lankan, Laos, and Chinese local chickens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the efficiency of this analysis relies on heterozygotes across genomes [ 39 ], the result from low-coverage genomes is unreliable. The number of high-coverage genomes in 1K CGP is limited [ 27 ], so we also included recently published chicken genomes [ 35 , 40 , 41 ] with a coverage of ≥ 20-folds in this analysis (Additional file 1 : Table S1). Our data contain genomes from GGS and 18 chicken populations including commercial breeds (White Leghorn, White Recessive Rocks, Rhode Island Red, and Cobb chicken), Ethiopian, Sri Lankan, Laos, and Chinese local chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Pair-wise sequential Markovian coalescent (PSMC) [ 38 ] and multiple sequential Markovian coalescent (MSMC) analyses require high-coverage genomes for the successful calling of genome-wide heterozygosity. We selected high-coverage genomes from previous studies (find detail in Additional file 1 : Table S1) [ 35 , 40 , 41 , 74 ], including genomes for GGS and 18 diverse chicken populations (Yunnan chicken, Yunnan game fowl, Emei chicken, Muchuan chicken, Hetian chicken, Tulufan chicken, Lindian chicken, Liyang chicken, Xianju chicken, Baier Yellow chicken, Yunyang Da chicken, Laos chicken, Sri Lankan chicken, Ethiopian chicken, and four European commercial chicken breeds (White Recessive Rocks, Cobb chicken, White Leghorn, and Rhode Island Red)). All reads from these samples were mapped to the chicken reference genome (GRCg6a: https://www.ncbi.nlm.nih.gov/assembly/?term=GCA_000002315.5 ) using the standard BWA-GATK pipeline [ 78 , 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…The newfound basal position patterns of Philippine RJFs in subhaplogroup D2 are grouped together with one of the early recorded Chinese gamecocks -Tulufan and the oldest Jidori-type breed in Japan -the Tosa-Jidori. The ancestral origin of Tosa-Jidori is suggested from the ISEA (Oka et al, 2007), while the ancestral origin of haplogroup D Tulufan gamecock in Northwest China is ambiguous because its diversity of distribution is mostly concentrated in haplogroups A and C (Miao et al, 2013), and independent admixture among gamecock breeds is evident (Luo et al, 2020). However, recent reports using whole-genome sequences showed a possible contribution of the local RJF subspecies or the earlier admixed domestic lineages from Yunnan Province, China, and MSEA (Luo et al, 2020;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the phylogenetic tree indicated genetic differentiation in DRD2 and ADGRG6 between the Line B chickens and the small-sized breeds because the former could not be completely separated from the Chahua and Daweishan mini chickens when five random-selected 100 Kb regions were used. In the selective sweep analysis of chickens, windows with thresholds of 1 or 5% outliers were typically identified as candidate regions ( Yin et al, 2019 ; Li W. et al, 2020 ; Luo et al, 2020 ; Weng et al, 2020 ). The F ST values in ADGRG6 reached the top 5% threshold, whereas the log 2 ⁡(π ratio ) values and zHp values reached the top 10% threshold of the whole genome.…”
Section: Discussionmentioning
confidence: 99%